Modelling volatility in Indian currency market. (2016) - Mittal, Sanjiv; Kumar, Ashish
The present paper aims at studying the relationship between volatility in the exchange rate in the spot market and trading activity in the currency futures market. The data used in this paper comprises of daily exchange rate of USD in terms of Indian rupees for the sample period 1 January 2006 to 12 September 2011. The volatility of the exchange rates has been measured by applying suitable GARCH model. For establishing the feedback causality between the volatility in the spot exchange rate and trading activity in the currency futures market Granger causality test has been applied. The results of the study report a significant difference in the mean volatility in spot exchange rates return in pre futures period and post futures period. The estimated mean volatility is higher in post futures period indicating that futures have resulted in increase in the spot exchange rate returns. Further, the results of Granger causality test establish the bi-directional relationship between volatility in exchange rate returns and volumes in currency futures.